Use of automatic image classification for analysis of the landscape, case study of Staré Jesenčany, the Czech Republic - Trojovská, Eva; Sedlák, Pavel; Komárková, Jitka; Čermáková, Ivana (Springer International Publishing AG, 2018)
The landscape is changing, mainly due to man. The changes in the landscape are increasingly important, so it is important to monitor these changes, mainly due to the use of resources in the country in the future. The article deals with the use of automatic classification of data from remote sensing to analyse the development of the landscape on the case study in the village Staré Jesenčany, the Czech Republic.
Využití automatické klasifikace snímků pro analýzy krajiny, případová studie Staré Jesenčany, Česká republika
Keywords: Automatic classification; Comparison of classification; Image processing; Landscape changes; automatická klasifikace; porovnání výsledků klasifikace; zpracování obrazu; změny krajiny